Model Predictive Optimization Control Strategy for Three-level AFE Converter - Xiaoyan Shi; Longji Zhu; Shuijuan Yu (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2016)
In view of the fact of traditional MPC prediction for three-level AFE converter with numerous switching vectors, time-cost computation and complex control, a simplified model predictive control algorithm is proposed in this paper. The multiple current prediction is transformed into a single virtual reference voltage vector prediction according to the inverse procedure of the model current prediction, and vector distribution method is adopted which can screens out the optimal vector. In the process of rolling optimization, multi-objective control is carried out by adding neutral point potential balance and reducing switching losses and other constraints to the cost function. Also the control delay of the algorithm is compensated. Finally, simulation experiments of three-level AFE converter under steady-state and dynamic conditions are provided. The results have verified correctness and practicability of the strategy.